2011
DOI: 10.1002/jmv.22140
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of group C rotavirus in children with acute gastroenteritis in Brazil: An emergent epidemiological issue after rotavirus vaccine?

Abstract: Group C rotavirus (GpCRV) has a worldwide distribution; however, its epidemiology and ecology are still unclear. Evidence for a possible zoonotic role has been postulated recently for Brazilian children strains. The aim of this study was to monitor GpCRV in children ≤15 years with acute gastroenteritis during the 2007-2010 national Brazilian rotavirus surveillance, and to undertake the molecular characterization of the major VP6 capsid protein. A total of 3,019 fecal samples were first screened for Group A rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…This may be explained by the high vaccination coverage in São José do Rio Preto (99%), which provides protection against the most common rotavirus, species A 37 . Indeed, studies in several countries have shown that rotavirus species C is not as uncommon as thought, however its prevalence is low (0.4-35%) 15 , 17 , 26 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the high vaccination coverage in São José do Rio Preto (99%), which provides protection against the most common rotavirus, species A 37 . Indeed, studies in several countries have shown that rotavirus species C is not as uncommon as thought, however its prevalence is low (0.4-35%) 15 , 17 , 26 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…c o m / l o c a t e / m e e g i d system, defining G and P-types respectively (Estes and Kapikian, 2007). Although an official classification system for RVC has not been established, at least 11 VP7 genotypes, nine VP4 genotypes and 11 VP6 genotypes have been reported to date (Araújo et al, 2011;Eren et al, 2016;Jeong et al, 2015;Kumazaki and Usuku, 2014;Lee et al, 2011;Lobo Pdos et al, 2016;Luchs et al, 2011;Luchs and do Carmo, 2015;Marthaler et al, 2013;Médici et al, 2010;Mitui et al, 2009;Moon et al, 2011;Moutelíková et al, 2014;Moutelíková et al, 2015;Park et al, 2011;Peng et al, 2013;Possatti et al, 2016;Suzuki et al, 2014;Stipp et al, 2015;Suzuki et al, 2015;Theuns et al, 2015;Zhirakovskaia et al, 2016). In RVA, extensive genetic variation has resulted in the accumulation of large numbers of RVA genotypes in animals, therefore an extended classification system assigning genotype to each of the 11 segments was provided by the Rotavirus Classification Working Group (Matthijnssens et al, 2008b(Matthijnssens et al, , 2011.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 95%
“…To date, RVCs have been detected in humans, cows, ferrets and dogs (Rodger et al , 1982; Torres-Medina, 1987; Tsunemitsu et al , 1991; Chang et al , 1999; Otto et al , 1999; Mawatari et al , 2004). Human RVCs have been detected not only exclusively in children under 3 years old, but also in all age groups including adults in many countries (Peñaranda et al , 1989; Kuzuya et al , 1998; Matsumoto et al , 1989; Qiao et al , 1999; Nilsson et al , 2000; Adah et al , 2002; Castello et al , 2002; Mwenda et al , 2003; Sánchez-Fauquier et al , 2003; Phan et al , 2004; Schnagl et al , 2004; Rahman et al , 2005; Abid et al , 2007; Esona et al , 2008; Gabbay et al , 2008; Medici et al , 2009; Mitui et al , 2009; Luchs et al , 2011; Moon et al , 2011). However, the prevalence of RVC in gastroenteric disease of children was reported to be relatively low, in spite of the global distribution of the virus (Mackow, 1995).…”
Section: Introductionmentioning
confidence: 99%